The Changing Epidemiology of Candidemia in the United States: Injection Drug Use as an Increasingly Common Risk Factor—Active Surveillance in Selected Sites, United States, 2014–2017. (2nd November 2019) - Zhang, Alexia Y; Shrum, Sarah; Williams, Sabrina; Petnic, Sarah; Nadle, Joelle; Johnston, Helen; Barter, Devra; Vonbank, Brittany; Bonner, Lindsay; Hollick, Rosemary; Marceaux, Kaytlynn; Harrison, Lee; et al.
Abstract: Background: Injection drug use (IDU) is a known, but infrequent risk factor on candidemia; however, the opioid epidemic and increases in IDU may be changing the epidemiology of candidemia. Methods: Active population-based surveillance for candidemia was conducted in selected US counties. Cases of candidemia were categorized as IDU cases if IDU was indicated in the medical records in the 12 months prior to the date of initial culture. Results: During 2017, 1191 candidemia cases were identified in patients aged >12 years (incidence: 6.9 per 100 000 population); 128 (10.7%) had IDU history, and this proportion was especially high (34.6%) in patients with candidemia aged 19–44. Patients with candidemia and IDU history were younger than those without (median age, 35 vs 63 years; P < .001). Candidemia cases involving recent IDU were less likely to have typical risk factors including malignancy (7.0% vs 29.4%; relative risk [RR], 0.2 [95% confidence interval CI, .1–.5]), abdominal surgery (3.9% vs 17.5%; RR, 0.2 [95% CI, .09–.5]), and total parenteral nutrition (3.9% vs 22.5%; RR, 0.2 [95% CI, .07–.4]). Candidemia cases with IDU occurred more commonly in smokers (68.8% vs 18.5%; RR, 3.7 [95% CI, 3.1–4.4]), those with hepatitis C (54.7% vs 6.4%; RR, 8.5 [95% CI, 6.5–11.3]), and in people who were homeless (13.3% vs 0.8%; RR, 15.7 [95% CI, 7.1–34.5]). Conclusions: Clinicians should consider injection drug use as a risk factor in patients with candidemia who lack typical candidemia risk factors, especially in those with who are 19–44 years of age and have community-associated candidemia. Abstract : Surveillance for candidemia across 9 US states during 2017 revealed that 10.7% of cases involved recent injection drug use (IDU)—unexpectedly high for what is primarily a healthcare-associated infection. The opioid crisis and concomitant IDU may be shifting the epidemiology of candidemia.